Isolated flat desmoid-type terminal ileal mesenteric fibromatosis masquerading as lower ureteric stricture-an intraoperative surprise - Karthikeyan, Aswathaman (Turk J Urol, 2019)
Ureteral strictures are usually caused by ureteral calculi, endoscopic instrumentation, infections like tuberculosis, surgical dissection, radiation, malignancy and periureteral fibrosis. A 42-year-old man presented with right loin pain 2 months previously. Contrast-enhanced computed tomography showed right lower ureteral stricture and he was scheduled for right ureteral reimplantation. Intraoperatively, a large hard mass arising from the mesentery of the terminal ileum infiltrating the retroperitoneum and encasing the right external iliac artery, vein and ureter was identified. The mass was resected and psoas hitch was performed over a 5F (26 cm) double J stent. Patient was discharged on tenth postoperative day and is still doing well at 18 months of follow up period. We are reporting this case to highlight the rare possibility of mesenteric fibromatosis and its management.